2020
DOI: 10.1093/jhps/hnaa065
|View full text |Cite
|
Sign up to set email alerts
|

Overcorrection of the acetabular roof angle or anterior center–edge angle may cause decrease of range of motion after curved periacetabular osteotomy

Abstract: The aim of this study was to evaluate the relationship between the correction of radiographic parameters and clinical range of motion (ROM) after periacetabular osteotomy (PAO). Sixty-nine patients with hip dysplasia were enrolled and underwent curved PAO. The pre- and post-operative 3D center–edge (CE) angles, total anteversion (acetabular and femoral anteversion), and radiographic acetabular roof angle were measured and compared with the post-operative ROM. The aim of surgery was to rotate the central acetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…Hamada et al reported that the mean femoral anteversion was similar between patients with postoperative anterior impingement and nonimpingement after RAO 16 . We previously reported that combined anteversion was significantly correlated with flexion and IR after curved PAO 12 . However, research on the correlation between combined anteversion and postoperative clinical outcomes after PAO is rare.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Hamada et al reported that the mean femoral anteversion was similar between patients with postoperative anterior impingement and nonimpingement after RAO 16 . We previously reported that combined anteversion was significantly correlated with flexion and IR after curved PAO 12 . However, research on the correlation between combined anteversion and postoperative clinical outcomes after PAO is rare.…”
Section: Discussionmentioning
confidence: 91%
“…16 We previously reported that combined anteversion was significantly correlated with flexion and IR after curved PAO. 12 However, research on the correlation between combined anteversion and postoperative clinical outcomes after PAO is rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgeons try to achieve a horizontal acetabular weight-bearing area [ 4 ] with PAO while ensuring that the osteotomy sites stay in contact to avoid nonunion. The acetabular inclination (AI) angle should be between 0° and 10°, whereas the CE angle is aimed to be approximately 35° for the best outcome, according to Hartig-Andreasen [ 5 ].…”
Section: Introductionmentioning
confidence: 99%